Discriminant Analysis to Predict Workers Wanted to Find Other Job - Haq, Muhammad Faiz El; Sihombing, Pardomuan Robinson (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tadulako, 2021)
This study aims to produce a model function that can predict whether a worker wants to find another job or not by looking at demographic characteristics such as age and job characteristics such as length of work in the main job, working hours during the past month, and income received. The variables observed were age, length of work in the primary position, working hours during the past month, and income. The dependent variable is the desire to find another job. The research sample used secondary data, namely the results of the 2017 National Labor Force Survey (SAKERNAS) conducted by the Central Statistics Agency of Padang Panjang City. Based on the analysis results, the discriminant function contains significant Age and income variables with a negative correlation for age and a positive correlation for income.